Use of thermography in skin grafts after the application of therapeutic ultrasound in wistar rats - da Silveira, Ynaiê Garcia [UNESP]; Kajiura, Caroline [UNESP]; Bernardes, Filippo Jannoni Lessa [UNESP]; Maria, Sônia Prince [UNESP]; Fernandes, Marina Pugnaghi [UNESP]; Frasson, Marla Tereza [UNESP]; Cassino, Pedro [UNESP]; Moreira, Stella Habib [UNESP]; Gómez, Jorge Luis Álvarez [UNESP]; Pazzini, Josiane Morais; de Nardi, Andrigo Barboza [UNESP]; Moraes, Paola Castro [UNESP] (FapUNIFESP (SciELO), 2020)
Purpose: To analyze changes in the thermal pattern in the skin graft receptor bed, after the use of therapeutic ultrasound through the thermographic images. Methods: Eighteen Rattus norvegicus albinus Wistar, separated into two groups: GST groups (without tumor and without treatment with ultrasound) and GT (with tumor and treatment with ultrasound). In the GT group, induction of carcinogenesis was performed by single intradermal application of 0.05 ml DMBA at 0.5%, diluted in acetone. Subsequently, a technique of reconstructive grafting surgery of the mesh type was performed in both groups and treatment with therapeutic ultrasound was performed in the GT group the alternate day protocol at 3, 6, 10 and 15 days after the procedure. The thermographic evaluation occurred on days 3, 6, 10 and 15 after the grafting. Results: There was a significant difference between the statistical evaluation of the temperature of the control group when compared to the treated group, on the different evaluation days (p <0.0001). Conclusion: The thermographic analysis of the images was effective in evaluating the healing process, being the use of thermography feasible to evaluate changes in the thermal standard in the surgical bed, besides the beneficial effects of the US.
Keywords: Rats; Skin; Thermography